Evaluating the physical and basic gymnastics skills assessment for talent identification in men`s artistic gymnastics proposed by the International Gymnastics - Mkaouer, B.; Hammoudi-Nassib, S.; Amara, S.; Chaabene, H. (Biology of Sport, 2018)
This study aimed to determine the specific physical and basic gymnastics skills considered critical in gymnastics talent identification and selection as well as in promoting men`s artistic gymnastics performances. Fifty-one boys from a provincial gymnastics team (age 11.03 ± 0.95 years; height 1.33 ± 0.05 m; body mass 30.01 ± 5.53 kg; body mass index [BMI] 16.89 ± 3.93 kg/m²) regularly competing at national level voluntarily participated in this study. Anthropometric measures as well as the men`s artistic gymnastics physical test battery (i.e., International Gymnastics Federation [FIG] age group development programme) were used to assess the somatic and physical fitness profile of participants, respectively. The physical characteristics assessed were: muscle strength, flexibility, speed, endurance, and muscle power. Test outcomes were subjected to a principal components analysis to identify the most representative factors. The main findings revealed that power speed, isometric and explosive strength, strength endurance, and dynamic and static flexibility are the most determinant physical fitness aspects of the talent selection process in young male artistic gymnasts. These findings are of utmost importance for talent identification, selection, and development.